Towards a 'Sea‐Level Sensitive' dynamic model: impact of island ontogeny and glacio‐eustasy on global patterns of marine island biogeography. (4th January 2019) - Ávila, Sérgio P.; Melo, Carlos; Berning, Björn; Sá, Nuno; Quartau, Rui; Rijsdijk, Kenneth F.; Ramalho, Ricardo S.; Cordeiro, Ricardo; De Sá, Nuno C.; Pimentel, Adriano; Baptista, Lara; Medeiros, António; et al.
ABSTRACT: A synthetic model is presented to enlarge the evolutionary framework of the General Dynamic Model (GDM) and the Glacial Sensitive Model (GSM) of oceanic island biogeography from the terrestrial to the marine realm. The proposed 'Sea‐Level Sensitive' dynamic model (SLS) of marine island biogeography integrates historical and ecological biogeography with patterns of glacio‐eustasy, merging concepts from areas as diverse as taxonomy, biogeography, marine biology, volcanology, sedimentology, stratigraphy, palaeontology, geochronology and geomorphology. Fundamental to the SLS model is the dynamic variation of the littoral area of volcanic oceanic islands (defined as the area between the intertidal and the 50‐m isobath) in response to sea‐level oscillations driven by glacial–interglacial cycles. The following questions are considered by means of this revision: ( i ) what was the impact of (global) glacio‐eustatic sea‐level oscillations, particularly those of the Pleistocene glacial–interglacial episodes, on the littoral marine fauna and flora of volcanic oceanic islands? ( ii ) What are the main factors that explain the present littoral marine biodiversity on volcanic oceanic islands? ( iii ) How can differences in historical and ecological biogeography be reconciled, from a marine point of view? These questions are addressed by compiling the bathymetry of 11 Atlantic archipelagos/islands to obtain quantitative data regarding changes in the littoral area based on Pleistocene sea‐level oscillations, from 150 thousand years ago (ka) to the present. Within the framework of a model sensitive to changing sea levels, we discuss the principal factors affecting the geographical range of marine species; the relationships between modes of larval development, dispersal strategies and geographical range; the relationships between times of speciation, modes of larval development, ecological zonation and geographical range; the influence of sea‐surface temperatures and latitude on littoral marine species diversity; the effect of eustatic sea‐level changes and their impact on the littoral marine biota; island marine species–area relationships; and finally, the physical effects of island ontogeny and its associated submarine topography and marine substrate on littoral biota. Based on the SLS dynamic model, we offer a number of predictions for tropical, subtropical and temperate volcanic oceanic islands on how rates of immigration, colonization, in‐situ speciation, local disappearance, and extinction interact and affect the marine biodiversity around islands during glacials and interglacials, thus allowing future testing of the theory.